Parameters Affecting Conscious Versus Unconscious Visual Discrimination with Damage to the Visual Cortex (V1) - Weiskrantz, Lawrence; Barbur, John L.; Sahraie, Arash (Proceedings of the National Academy of Sciences - PNAS, 1995)
When the visual (striate) cortex (V1) is damaged in human subjects, cortical blindness results in the contralateral visual half field. Nevertheless, under some experimental conditions, subjects demonstrate a capacity to make visual discriminations in the blind hemifield (blindsight), even though they have no phenomenal experience of seeing. This capacity must, therefore, be mediated by parallel projections to other brain areas. It is also the case that some subjects have conscious residual vision in response to fast moving stimuli or sudden changes in light flux level presented to the blind hemifield, characterized by a contentless kind of awareness, a feeling of something happening, albeit not normal seeing. The relationship between these two modes of discrimination has never been studied systematically. We examine, in the same experiment, both the unconscious discrimination and the conscious visual awareness of moving stimuli in a subject with unilateral damage to V1. The results demonstrate an excellent capacity to discriminate motion direction and orientation in the absence of acknowledged perceptual awareness. Discrimination of the stimulus parameters for acknowledged awareness apparently follows a different functional relationship with respect to stimulus speed, displacement, and stimulus contrast. As performance in the two modes can be quantitatively matched, the findings suggest that it should be possible to image brain activity and to identify the active areas involved in the same subject performing the same discrimination task, both with and without conscious awareness, and hence to determine whether any structures contribute uniquely to conscious perception.